2012
DOI: 10.1099/mic.0.054031-0
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma reesei RUT-C30 – thirty years of strain improvement

Abstract: The hypersecreting mutant Trichoderma reesei RUT-C30 (ATCC 56765) is one of the most widely used strains of filamentous fungi for the production of cellulolytic enzymes and recombinant proteins, and for academic research. The strain was obtained after three rounds of random mutagenesis of the wild-type QM6a in a screening program focused on high cellulase production and catabolite derepression. Whereas RUT-C30 achieves outstanding levels of protein secretion and high cellulolytic activity in comparison to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
289
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(320 citation statements)
references
References 94 publications
4
289
0
6
Order By: Relevance
“…Pycnoporus sp. produced the highest cellulase activity of 0.23 FPU/ml, which is comparable to the activities produced by the wild type filamentous fungus Trichoderma reesei QM6a (Mandels, 1975), which is the parent strain of the mutant strain Trichoderma reesei RUT-C30, used for industrial production of cellulases (Peterson and and Nevalainen, 2012). The highest xylanase activity of 5.4 U/ml was produced by Phlebiopsis sp.…”
Section: Isolation Identification and Screening Of Enzyme Activitiessupporting
confidence: 48%
“…Pycnoporus sp. produced the highest cellulase activity of 0.23 FPU/ml, which is comparable to the activities produced by the wild type filamentous fungus Trichoderma reesei QM6a (Mandels, 1975), which is the parent strain of the mutant strain Trichoderma reesei RUT-C30, used for industrial production of cellulases (Peterson and and Nevalainen, 2012). The highest xylanase activity of 5.4 U/ml was produced by Phlebiopsis sp.…”
Section: Isolation Identification and Screening Of Enzyme Activitiessupporting
confidence: 48%
“…Table 2 Maximum values of volumetric productivity observed for production of cellulases by T. harzianum L04 strain grown on different carbon sources analyzed in this work, L04 showed a shorter acclimation period when cultivated in a complex substrate such as SCB. This observation is particularly interesting when compared to T. reesei Rut C30, a widely used filamentous fungus strain used for the production of cellulolytic enzymes (Peterson and Nevalainen 2012). T. reesei Rut C30 shows a longer acclimation to lignocellulosic feedstock and is known to have a better performance for cellulase production when grown on pure cellulosic substrates then on lignocellulosic ones (Juhász et al 2005), data confirmed by Castro et al (2010c) where maximum values of volumetric productivity for T. reesei Rut C30 were obtained at 333 hours culture.…”
Section: Discussionmentioning
confidence: 99%
“…This may be result of a bias in isolation or sequencing of cellulolytic organisms, or by a lower number of Gram-negative cellulolytic organisms in the environment. No Gram-negative organism possesses a cellulolytic set of enzymes comparable to either the Gram-positive sets of cellulases described above or the fungal set described for T. reesei [7,59]. Of the Gramnegatives, Cellvibrio japonicus appears to have the most 'normal' collection of cellulases (Supplementary Table M).…”
Section: Cellulose Degradation By Soluble Enzymes Of Cellvibriomentioning
confidence: 99%